(Controlled) Free radical (co)polymerization of multivinyl monomers: strategies, topological structures and biomedical applications. Issue 28 (15th March 2023) - Li, Zhili; Yong, Haiyang; Wang, Kaixuan; Zhou, Ya-Nan; Lyu, Jing; Liang, Lirong; Zhou, Dezhong
Abstract : Chemically and topologically complex polymers are synthesized by free radical (co)polymerization of multivinyl monomers and used for various biomedical applications. Abstract : Free radical (co)polymerization (FRP/FRcP) of multivinyl monomers (MVMs) has emerged as a powerful strategy for the synthesis of chemically and topologically complex polymers due to its unique reaction kinetics, which enables the preparation of polymers with multiple functional groups and novel macromolecular structures. However, conventional FRP/FRcP of MVMs inevitably leads to insoluble crosslinked materials. Therefore, the development of advanced strategies for the controlled polymerization of MVMs is essential for the preparation of chemically and topologically complex polymers. In this review, we introduce the gelation mechanism of conventional FRP of MVMs and present the strategies of controlled polymerization of MVMs for the preparation of chemically and topologically complex polymers. We also discuss polymers with unique topologies synthesized by controlled polymerization of MVMs, such as crosslinked networks, (hyper)branched, star, cyclic, and single-chain cyclized/knotted structures. Finally, biomedical applications of various advanced polymeric materials prepared by controlled polymerization of MVMs are highlighted and the challenges is this field are discussed.